Association of polymorphic variants of ADRB1 gene with contractile myocardial dysfunction and erythrocyte adrenoreactivity in patients with rhythm disorders - S. A. Afanasiev; T. Yu. Rebrova; E. F. Muslimova; E. V. Borisova (Российский кардиологический журнал)
Aim. To study the association of the rs1801252 (A145G, Ser49Gly) and rs1801253 polymorphic variants (G1165C, Gly389Arg) of the p1-adrenoreceptor ADRB1 gene with the clinical manifestations of chronic heart failure (CHF) and the adrenoreactivity of their erythrocyte membranes in patients with cardiac arrhythmias.Material and methods. The study included 47 patients with atrial fibrillation and I-III FC CHF. A standard clinical examination of patients was performed, including a six-minute walk test and an echocardiographic study. The rs1801252 (A145G, Ser49Gly), rs 1801253 (G1165C, Gly389Arg) polymorphic variants of the p1-adrenoceptor ADRB1 gene and p-adrenoreactivity of erythrocyte membranes were determined.Results. A statistically significant inverse correlation of p-adrenoreactivity of erythrocyte membranes with the left ventricular ejection fraction (r=-0,336, p=0,021) and a direct correlation with the end-systolic volume (r=0,320, p=0,039) were defined. Depending on the FC of CHF, there was a pronounced tendency (p=0,058) of p-adrenoreactivity increasing. In patients with I FC — 25,88 (12,07; 46,37) relative units, II FC — 30,54 (14,50; 43,36) relative units, III FC — 3774 (33,67; 41,81) relative units. Diastolic dysfunction in patients was combined with a decrease in the adrenoreactivity of the organism. The median of p-adrenoreactivity of erythrocyte membranes in the group of patients with diastolic dysfunction was significantly (p=0,021) higher (33,04 (16,30; 4729) relative units) than in the group without diastolic dysfunction (15,91 (11,10; 26,47) relative units). In the studied sample, there were no statistically significant differences in the frequency of diastolic dysfunction in carriers of different genotypes of the rs1801252 and rs1801253 polymorphic variants of the ADRB1 gene (p=1,0 and p=0,058, respectively). An association (p=0,042) of a carrier of the homozygous 145AA rs1801252 genotype with high p-adrenoreactivity of erythrocyte membranes (32,5 (14,6; 473) relative units) was detected in comparison with the heterozygous 145AG genotype (16,3 (11,7; 31,5) relative units). In the studied sample, there was no statistically significant association of p-adrenoreactivity with the carrier of homozygous and heterozygous genotypes of the rs1801253 variant of the ADRB1 gene.Conclusion. The studied rs1801252 and rs1801253 variants of the ADRB1 gene have different associations with impaired diastolic function of the myocardium and desensitization of erythrocyte p-adrenoreceptors.